Gov-arrrgh-nance: Jolly Rogers and Dodgy Rulers - Olaf J. de Groot; Anja Shortland (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
In this paper, we argue that the effect of governance on the emergence of crimes of different levels of sophistication is highly non-linear. State failure, anarchy and a lack of infrastructure are not conducive to establishing any business, including illicit enterprises. At the bottom of the spectrum, therefore, both legal business and criminal gangs benefit from improved governance. With further improvements in governance criminal activities decline. We find strong and consistent support for this hypothesis using the International Maritime Bureau's dataset on piracy. Piracy is reported by ship-owners, giving a unique insight into crime in badly governed countries which were systematically excluded from previous analyses. We show that profitable forms of piracy flourish where on the one hand there is stability and infrastructure, but on the other hand the state does not have the capacity to intervene and/or bureaucrats can be bribed to turn a blind eye. For minor acts of theft from ships the pattern is quadratic: piracy first rises and then falls as governance improves.
Keywords: K42; P48; 330; Piracy; illegal behaviour; law enforcement; legal institutions